Psikologi Pendidikan Islam Dalam Proses Pembelajaran : Tinjauan Literatur Sistematis dan Implikasinya terhadap Pengembangan Karakter Peserta Didik - Ifratul Hasanah; Muhammad Ghildan Akmal; M. Ghoris Hoirul; Mu’alimin Mu’alimin (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
Islamic educational psychology is one of the important foundations in the learning process thatis not only oriented toward the mastery of knowledge but also toward the development of students’character. In the context of modern education, the integration of psychological and spiritual values inlearning has become increasingly important to create a holistic educational process. This article aims toexamine how the concept of Islamic educational psychology is applied in the learning process and itsimplications for the development of students’ character. The research questions in this study are: (1) howthe concept of Islamic educational psychology is discussed in the scientific literature, and (2) how itinfluences character formation in the learning process.This study uses a systematic literature review methodby searching for articles in several academic databases such as Google Scholar, Garuda, and Sinta. Thesearch was conducted using the keywords “Islamic educational psychology,” “learning,” and “students’character.” From the literature selection process of articles published between 2015–2024, 20 relevantarticles were obtained for analysis.The results of the review indicate that Islamic educational psychologyemphasizes a balance between cognitive, affective, and spiritual aspects in the learning process. In addition,the literature shows that this approach plays an important role in shaping moral values, religious attitudes,and students’ learning motivation. In conclusion, Islamic educational psychology has a significantcontribution to the development of students’ character through an integrative learning process. Futureresearch is recommended to examine the empirical implementation of this concept in various Islamiceducational institutions.